A study on the willingness of undergraduate nursing students to participate in Time Banking voluntary pension service (护理本科学生参与"时间银行"志愿养老服务意愿的原因及影响因素分析) - LI Chunxiang (李春香); XU Shuli (徐数理); MA Jing (马敬); ZHANG Ying (张莹) (Journal of International Translational Medicine Limited, 2021)
Objective To understand the willingness of undergraduate nursing students to participate in Time Banking voluntary pension service and analyze the reasons that affect the willingness of undergraduate nursing students to participate. Methods Totally 208 students in a certain university of Luoyang were investigated with self-designed questionnaire about willingness of Time Banking voluntary elderly care service. Results Totally 94. 71%(197/208)of the students were willing to participate in the Time Banking voluntary pension service, and they had different understandings on the service provided by the Time Banking service. The results of chi square test showed that age, gender, political status, whether to engage in medical related majors had an impact on the time saving willingness of nursing undergraduates (P＜0. 05). Conclusion Multiple factors influence the willingness of undergraduate nursing students to participate and provide volunteer care in a variety of ways. (目的 了解高校护理本科学生参与"时间银行"志愿养老服务的意愿, 分析影响护理本科学生参与意愿的原因。方法 采用自行设计的"时间银行"志愿养老服务意愿调查问卷, 对洛阳市某本科护理院校208名学生进行问卷调查。结果 94. 71%(197/208)学生愿意参加"时间银行"志愿养老服务, 学生在"时间储蓄"志愿养老提供的服务等内容上有不同理解。卡方检验结果分析显示年龄、性别、政治面貌、是否从事医学相关专业对护理本科学生的"时间银行"志愿养老服务意愿有影响(P＜0. 05)。结论 高校护理本科生愿意参与并提供多方面的志愿照护服务, 多种因素影响学生的志愿服务意愿。)